Decoding Frontotemporal Dementia: Genes, Proteins and Prospects for Precision Medicine - Kaushik Raj; Nandani Kumari; Pragya Bharti; Ranjeet Kumar; Dharmendra Kumar (Current Alzheimer Research, 2026)
Frontotemporal Dementia is an umbrella term for several neurodegenerative disorders that have a similar presentation pattern, which is accompanied by neural damage and brain tissue loss in the frontal and temporal regions. Recent studies have observed that the heterogeneity of Frontotemporal Dementia (FTD) is reflected in clinical features, genetics, and molecular perspectives. Specifically, the major forms of pathology in FTD are linked to abnormal protein accumulation, which includes tau, TAR DNA-binding protein 43 (TDP-43), and fused in sarcoma (FUS). Moreover, genetic research on FTD has identified vital mutations in MAPT (Microtubule-associated protein Tau), GRN (Progranulin Gene), and C9ORF72 genes (Chromosome 9 open reading frame genes). Recent developments in neuroimaging, biomarker levels in body fluids, and molecular profiling have increased diagnostic precision, enabling earlier detection of disease subtypes. Neurofilament light chain (NfL), progranulin, and several other biomarkers, together with novel neuroimaging approaches, are currently being applied for disease classification, prognosis, and disease treatment monitoring. These developments have accelerated the application of precision medicine for FTD, including antisense oligonucleotides, progranulin-restorative drugs, tau-specific therapies, and gene therapy. Despite advances in elucidating the biology of FTD, no disease-modifying therapies have yet been developed, and treatments remain symptomatic until now. Undoubtedly, there are many challenges when taking into account variable presentation, overlapping pathologies, and the lack of robust biomarkers. The aim of this paper is to provide an in-depth analysis of the epidemiology, clinical features, molecular pathologies, biomarkers, and potential therapeutic approaches concerning FTD, with a particular emphasis on the growing role of precision medicine. Omics technologies, biomarker- based patient stratification, and hypothesis-driven clinical trials are undoubtedly essential steps towards personalized therapy for FTD.